(untitled) (TEST Ticontre. Theory Text Translation, 2025)
With the metaphor of the visiting rooms, Portuguese poet Ana Luísa Amaral presents a conception of memory and revisitation, both personal and cultural, that reduces the distance between lived life and memory, whether individual or collective, embracing the coexistence and overlap of different times. In both realms—personal and cultural—a process takes place that we can define, borrowing the poet’s own terms, as one of inversion or reversal. Cultural, poetic, or historiographic revisitation is not merely a retelling of what is already known but becomes a rewriting that places the act of remembering within an intimate dimension, overturning traditional perspectives on memory. This reversal of traditional memory opens the way to a more inclusive cultural and historiographic vision, one that intertwines individual experiences with collective memory. The metaphor of the visiting rooms effectively captures the complexity of this approach, rooted in a balance between ethics, freedom, and intimacy in the act of remembering. Con la metafora delle sale delle visite, la poetessa portoghese Ana Luísa Amaral presenta una concezione del ricordo e della rivisitazione, sia personale che culturale, che riduce la distanza tra vita vissuta e memoria, individuale e collettiva, abbracciando la coesistenza e la coabitazione dei tempi. In entrambi gli ambiti – personale e culturale – si compie un’operazione che possiamo definire, riprendendo le parole della stessa poetessa, di inverso o rovescio. La rivisitazione culturale, poetica o storiografica, non si limita a essere un semplice retelling di ciò che è già noto, ma diventa una riscrittura che colloca l’atto di ricordare in una dimensione intima, capovolgendo le prospettive tradizionali della memoria. Questo rovesciamento della memoria tradizionale apre la strada a una visione culturale e storiografica più inclusiva, capace di intrecciare il vissuto privato con il ricordo collettivo. La metafora delle sale delle visite sintetizza con efficacia la complessità di questo approccio, radicato in un equilibrio tra etica, libertà e intimità nel ricordare.